PEMBINAAN KEAMANAN DAN KETERTIBAN MASYARAKAT (KAMTIBMAS) DI KELURAHAN PANGKALAN KERINCI BARAT - Rinawati, Evi; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Development of Community Security and Order (Kamtibmas) such as community order building, self-help security development, community policing development, and community potential development in Pangkalan Kerinci Barat Village through direct visits and socialization or the so-called door to door system is still not running optimally. The purpose of this study was to analyze how the formation of Community Service and what factors influence the formation of Kamtibmas in Pangkalan Kerinci Barat Village. This research was conducted in Pangkalan Kerinci Barat Village. The theory used in this research is Efendi's theory, with four indicators of community order development activities, self-help security fostering, community policing development, and community potential development. The research method used is qualitative qualification with data collection techniques through interviews, observation, and documentation. The selection of research informants using snowball sampling technique. The results of this study indicate that there are factors that influence the formation of Community Service in Pangkalan Kerinci Barat Village. These factors are human resources, communication and budget in activities related to the formation of Community Service in Pangkalan Kerinci Barat Village.Keywords: Implementation, Development, & Kamtibmas